2021
DOI: 10.1016/j.jtocrr.2021.100176
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Testing for People With Advanced Lung Cancer in England

Abstract: Introduction: Optimal management of people with advanced NSCLC depends on accurate identification of predictive markers. Yet, real-world data in this setting are limited. We describe the impact, timeliness, and outcomes of molecular testing for patients with advanced NSCLC and good performance status in England. Methods:In collaboration with Public Health England, patients with stages IIIB to IV NSCLC, with an Eastern Cooperative Oncology Group performance status of 0 to 2, in England, between June 2017 and De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 16 publications
(20 reference statements)
6
22
0
Order By: Relevance
“…Similar data has recently been published regarding advanced lung cancer patients in England with 71% of patients receiving TKI therapy on identification of an EGFR mutation 37. It was not clear from their paper which analysis method was used to detect EGFR mutation and they restricted their analysis to patients with a PS of 0, 1 and 2 37. The authors conclude that it is the timeliness of reporting EGFR mutation, in addition to anaplastic lymphoma kinase-1 (ALK-1) and PD-L1 status that is responsible for patients not receiving therapy for which they are eligible 37.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Similar data has recently been published regarding advanced lung cancer patients in England with 71% of patients receiving TKI therapy on identification of an EGFR mutation 37. It was not clear from their paper which analysis method was used to detect EGFR mutation and they restricted their analysis to patients with a PS of 0, 1 and 2 37. The authors conclude that it is the timeliness of reporting EGFR mutation, in addition to anaplastic lymphoma kinase-1 (ALK-1) and PD-L1 status that is responsible for patients not receiving therapy for which they are eligible 37.…”
Section: Discussionsupporting
confidence: 73%
“…A study by Ruggiero et al found a similar phenomenon with only 79% of EGFR positive advanced lung cancer patients in the US commenced on appropriate TKI therapy 36. Similar data has recently been published regarding advanced lung cancer patients in England with 71% of patients receiving TKI therapy on identification of an EGFR mutation 37. It was not clear from their paper which analysis method was used to detect EGFR mutation and they restricted their analysis to patients with a PS of 0, 1 and 2 37.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations